Design and implementation of collaborative multi agent robots in autonomous reconnaissance - Md. Masum Billah (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
Robots are gradually becoming omnipresent in daily life to take care of everyday chore like vacuuming floor, delivering food in hospital etc. However, these are examples of single robot activity. Difficult tasks like transporting big size objects inside factory floor or mapping of terrain for task planning demands multiple robots work in coordination. Groups of robots can solve problems in fundamentally different ways than individuals while achieving higher levels of performance. However, programming and coordination pose challenges on collaborative activity of all the robots inside a group. This work presents new collaborative algorithm for autonomous multi-agent robot for undertaking reconnaissance mission. A set of communication techniques, sharing behavior to get their position and appropriate attitude which is useful for a group of robots to work together for any kind of reconnaissance mission are developed. A modified gradient communications algorithm is presented here which is flexible to the constantly changing network topology of the multi-agent robots. This provides real-time information that is used to communicate data and to guide robots around the physical environment. Two hexapod robots equipped with inertial sensors like accelerometer and rate gyro are chosen for multi-agent robot navigation in 3D uneven terrain for their advantages over the traditional wheeled counterpart. The sharing behavior and coordination of motion are verified through experiments that built 3D map of a 5x5 m corrugated terrain. Two hexapod robots generated four thousand nodes in half an hour collaborating with each other while travelling over the terrain. Triangulation algorithm is then used for mapping 3D terrain using these nodes. Comparison of the new mapping algorithm with one of the existing algorithms shows that the new algorithm is superior to the existing one. In this research sensory signals are processed in a remotely located wireless connected computer. This poses limitation on the processing speed of data.